The prognostic value of sarcopenia combined with preoperative fibrinogen–albumin ratio in patients with intrahepatic cholangiocarcinoma after surgery: A multicenter, prospective study. (8th June 2021) - Yu, Haitao; Wang, Mingxun; Wang, Yi; Yang, Jinhuan; Deng, Liming; Bao, Wenming; He, Bangjie; Lin, Zixia; Chen, Ziyan; Chen, Kaiyu; Zhang, Baofu; Liu, Fangting; et al.
Abstract: Background: To explore the prognostic value of the fibrinogen–albumin ratio (FAR) combined with sarcopenia in intrahepatic cholangiocarcinoma (ICC) patients after surgery and to develop a nomogram for predicting the survival of ICC patients. Materials and Methods: In this prospective cohort study, 116 ICC patients who underwent radical surgery were enrolled as the discovery cohort and another independent cohort of 68 ICC patients was used as the validation cohort. Kaplan–Meier method was used to analyze prognosis. The independent predictor of overall survival (OS) and recurrence‐free survival (RFS) was evaluated by univariable and multivariable Cox regression analyses, then developing nomograms. The performance of nomograms was evaluated by concordance index (C‐index), calibration curve, receiver operating characteristic curve analysis (ROC), and decision curve analysis (DCA). Results: Patients with high FAR had lower OS and RFS. FAR and sarcopenia were effective predictors of OS and RFS. Patients with high FAR and sarcopenia had a poorer prognosis than other patients. OS nomogram was constructed based on age, FAR, and sarcopenia. RFS nomogram was constructed based on FAR and sarcopenia. C‐index for the nomograms of OS and RFS was 0.713 and 0.686. Calibration curves revealed great consistency between actual survival and nomogram prediction. The area under ROC curve (AUC) for the nomograms of OS and RFS was 0.796 and 0.791 in the discovery cohort, 0.823 and 0.726 in the validation cohort. The clinical value of nomograms was confirmed by the DCA. Conclusions: ICC patients with high FAR and sarcopenia had a poor prognosis, the nomograms developed based on these two factors were accurate and clinically useful in ICC patients who underwent radical resection. Abstract : Sarcopenia and high levels of FAR are related to the poor prognosis of ICC patients undergoing radical surgery. FAR and sarcopenia are convenient, inexpensive, and reliable marks that provide references for improving the prognosis and new treatment strategies for ICC patients after surgery.